Universidade corporativa: um instrumento a serviço da competitividade - Vahdat, Henri (2008)
The purpose of this work is to present a proposal of a corporate university that may assist organizations achieve new levels of productivity and competitiveness. The argument presented herein is that knowledge became a dominant factor in society s economic life and therefore must gain centrality in strategies of countries and corporations that aim to survive and prosper. In the ambit of corporations, in particular, corporate universities have proven to be an instrument for human capital development, amplifying the chances of organizational success in a world characterized by change, complexity and globalization. This dissertation is organized in four parts, along which the author fundaments his assumptions and propositions. Part I highlights the emergence of what some authors have called as the knowledge economy. We argue that knowledge is now the basic form of capital and that sustained economic growth in the new world economy depends on the successful conception of strategies that involve the use and creation of knowledge at the center of the process of economic development. Part II describes the scale and depth of the changes unleashed by the knowledge economy and the consequent need for a new enterprise organization centered in change, innovation, operational efficiency and sustainability. Part III discusses the origin, distinctive characteristics and the value that a corporate university may add to the business. Part IV analyzes two experiences of the concept s implementation one in Brazil and another one abroad that help to illustrate in what measure current corporate practices adhere to the proposed structure. The methodological approach consisted of exploratory research, with the purpose of advancing current propositions on the subject. The proposed model is utilized to assess the maturity level of two implementations of the concept in the corporate world. As conclusion, we underscore that corporate universities represent a clear evolution in comparison with current T&D departments and a privileged way of qualifying a company s workforce for the achievement of lasting competitive advantage. As a suggestion for future research, we recommend an investigation on the extent to which corporate universities help attract and retain the human capital of an organization